Some music traditions of Malawi - Strumpf, Mitchell (International Library of African Music, 1999)
Malawi, a country of great cultural diversity, shares many of its musical traditions with neighbouring cultures in other south-east African countries, namely Tanzania, Zambia, and Mozambique, as well as with culture groups further away, the Nguni (Zulu-Swazi) cultures of South Africa, for example. As part of the UNESCO CD series Musics and Musicians of the World, UNESCO (with AUVIDIS as co-publisher and distributor) made available Music traditions of Malawi (D 8265).
Keywords: African Music; Malawi; Music Tradition